Profession, Emotion, and Hope: Charlotte Perkins Gilman and the Origins of the Sociology of Gender - María Luisa Jiménez-Rodrigo (Redescriptions)
Charlotte Perkins Gilman (USA, 1860–1935) is considered one of the most significant feminist social theorists of her time. Despite this, she was excluded from the sociological canon for a long period. In contrast to her male counterparts, she proposed an alternative and pioneering theoretical framework for examining social reality, which placed gender domination at the forefront of sociological analysis. The ‘sexuo-economic relation’ and ‘androcentric culture’ are crucial concepts for understanding gender and social relations. This article presents a synthesis and review of the main pioneering contributions to the sociological analysis of gender. Gilman’s sociological thought challenges the androcentric and sexist nature of social science. She develops a theoretical framework for analysing gender domination on the basis of observations of inequality in everyday life. Gilman also implements an alternative model of sociological practice that is linked to social reform, outreach and social pedagogy to promote women’s emancipation and gender equality.